Edutainment technologies educational games and virtual reality/augmented reality applications :6th international conference on e-learning and games, edutainment 2011, Taipei, Taiwan, September 2011. proceedings - Chang, Maiga; Hwang, Wu-Yuin; Chen, Ming-Puu; Muller, Wolfgang (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on E-learning and Games, Edutainment 2011, held in Taipeh, Taiwan, in September 2011. The 42 full papers were carefully reviewed and selected from 130 submissions. The papers are organized in topical sections on: augemented and mixed reality in education; effectiveness of virtual reality for education; ubiquituous games and ubiquitous technology & learning; future classroom; e-reader and multi-touch; learning performance and achievement; learning by playing; game design and development; game-based learning/training; interactions in games; digital museum and technology, and behavior in games; educational robots and toys; e-learning platforms and tools; game engine/rendering/animations; game-assisted language learning; learning with robots and robotics education; e-portfolio and ICT-enhanced learning; game-based testing and assessment; trend, development and learning process of educational mini games; VR and edutainment.